2012
DOI: 10.1007/s00586-012-2439-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low back pain and factors associated with chronic disabling back pain in Japan

Abstract: Purpose This study aimed to report lifetime and 4-week low back pain (LBP) prevalence and examine factors associated with chronic LBP and back pain disability over a lifetime in a Japanese adult population. Methods In February 2011, 1,063,083 adults aged 20-79 years registered as internet research volunteers were randomly selected to participate in a questionnaire survey. The data from 65,496 respondents were analyzed to calculate age-standardized lifetime and 4-week prevalence. Chronic LBP and back pain disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(121 citation statements)
references
References 24 publications
5
112
3
1
Order By: Relevance
“…They asserted that it might be due to the significant heterogeneity existing among the LBP epidemiological reviews, restricting the capacity to think about it and pool information (6,7), and furthermore to a limited extent because of the lack of appropriate information. While, it is clear that individuals in all strata of society commonly experience LBP, its prevalence in a number of studies varies, which may be due to factors such as differences in social structure, economy of the developing and developed countries, population studied, environmental factors, and methodological issues, which influence the prevalence of LBP (8). Based on the the aforementioned diversity in epidemiological study of LBP, and paucity of regional or national representative data on LBP prevalence in Nigeria, the current review aimed at assessing the predominance of LBP in Nigeria.…”
Section: Contextmentioning
confidence: 99%
“…They asserted that it might be due to the significant heterogeneity existing among the LBP epidemiological reviews, restricting the capacity to think about it and pool information (6,7), and furthermore to a limited extent because of the lack of appropriate information. While, it is clear that individuals in all strata of society commonly experience LBP, its prevalence in a number of studies varies, which may be due to factors such as differences in social structure, economy of the developing and developed countries, population studied, environmental factors, and methodological issues, which influence the prevalence of LBP (8). Based on the the aforementioned diversity in epidemiological study of LBP, and paucity of regional or national representative data on LBP prevalence in Nigeria, the current review aimed at assessing the predominance of LBP in Nigeria.…”
Section: Contextmentioning
confidence: 99%
“…The first paper by Fujii and Matsudaira [22] was able by using an Internet survey, and shopping point rewards to look at a large number of people (77,709) and reach these people with a fairly detailed questionnaire. Although their definition of chronic pain as being more than 3 months was rather short, the overall figures they acquired, much the same as those in Europe and North America, of a lifetime prevalence of 83 % and, a 4-week prevalence of 36 %.…”
Section: Back Painmentioning
confidence: 99%
“…In Japan, back pain has a high lifetime incidence of 83.4% 4) . Kawakami 5) , who carried out a questionnaire survey of chronic back pain patients approximately 6 months after their initial examinations, found that almost all had discontinued treatment without an accurate outcome having been recorded, and that af ter 6 months, no patient responded that their pain had improved, 22.2% responded that it had improved temporarily but sometimes recurred, and 77.8% responded that they still had pain.…”
Section: Introductionmentioning
confidence: 99%